Low-molecular-weight thiols in streptomycetes and their potential role as antioxidants. - Newton, G L (1993)
The intracellular low-molecular-weight thiols present in five gram-positive Streptomyces species and one Flavobacterium species were analyzed by high-performance liquid chromatography after fluorescence labeling with monobromobimane. Bacteria were chosen to include penicillin and cephalosporin beta-lactam producers and nonproducers. No significant amount of glutathione was found in any of the streptomycetes. Major intracellular thiols in all strains examined were cysteine, coenzyme A, sulfide, thiosulfate, and an unknown thiol designated U17. Those streptomycetes that make beta-lactam antibiotics also produce significant amounts of delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine (ACV), a key intermediate in their biosynthesis. In Streptomyces clavuligerus, a potent producer of beta-lactams, the level of ACV was low during the early phase of growth and increased rapidly toward the end of exponential growth, paralleling that of antibiotic production. These and other observations indicate that ACV does not function as a protective thiol in streptomycetes. U17 may have this role since it was the major thiol in all streptomycetes and appeared to occur at levels about 10-fold higher than those of the other thiols measured, including ACV. Purification and amino acid analysis of U17 indicated that it contains cysteine and an unusual amine that is not one of the common amino acids. This thiol is identical to an unknown thiol found previously in Micrococcus roseus and Streptomyces griseus. A high level of ergothioneine was found in Streptomyces lactamdurans, and several unidentified thiols were detected in this and other streptomycetes.